An Instrument For The Salvation of the Soul: The Correction of the ‘Undisciplinated’ Clergy between Ius Vetus and Ius Novum (Italian Review of Legal History, 2022)
Some texts in Gratian’s Decretum (mostly by Augustine of Hippo and Gregory the Great as well as conciliar canons from the 6th and 7th centuries) dealt with the topic of the correction of regular and secular clergy by the hierarchical superiors, especially the bishop and the abbot. In a diocese, the bishop had to control the clerics subject to his authority personally – at least from a theoretical point of view. In a monastery, the same was true of the abbot, who had to act according the rule of his order. For this purpose, they had some ‘instruments’ to lead those who had infringed some rules, had disobeyed some orders, or had behaved badly – in other words, those who had been indisciplinated – to the ‘straight path’. Warning, exhorting or even threatening them were the first ways to go. Yet, however authoritative these warnings were, they risked being ignored if tools to make them effective were missing. The lawfulness and modality of exercising violence as an instrument of correction, chastisement, and punishment – commonly accepted at all levels of society, as it was also recommended by the Holy Scriptures –, however, did not clearly emerge from the chapters of Gratian. Indeed, on the one hand, some of them allowed it; on the other hand, some seemed to consider it with hesitation and set limits – or even prohibitions – since it was not convenient for men of the Church to resort to such means or to be subjected to them. One chapter, in particular, hampered seriously the use of force for disciplinary purposes. It was a later text (at least in its definitive formulation), that is the well-known can. 15 (Si quis suadente) of the Second Lateran Council (1139), which had introduced the physical intangibility of consecrated persons under penalty of excommunication. Thus, clerics gained sacredness, which seemed to make it very hard for the superior to use the traditional ‘educational’ tools. However, several decretals (by Alexander III, Celestine III, Innocent III, and Gregory IX) implemented the matter, providing for a series of exceptions to the so-called privilegium canonis. Therefore, those who exercised a legitimate power, which could therefore also be physical coercion over their subjects, did not take the risk of incurring excommunication. Canonists carried out the pivotal task of coordinating the various sources on this topic, above all by interpreting the texts of the Decretum in the light of the ius novum, trying to clearly define the limits, modalities, and scope of the powers of correction of the subjects who were fully legitimated to chastise clerics and monks to bound their immorality, divert them from their inclination to sin, and face their disobedience and indiscipline.
Keywords: Decretum; Decretals; Correction; Clergy; Excommunication